Targeted isolation of alkaloid from Cyclea Peltata and determination of structural formula of Tetrandrine alkaloid based on NMR studies - Rakesh Pillai; Alexander I Gray; Uma V.S (International Journal of Phytomedicine, 2010)
Alkaloids are group of chemical entity with proven medicinal properties. This work consolidates the procedure in isolation and structural determination of a bisbenzyl isoquinoline alkaloid from Cyclea peltata with related NMR values and data. Dried routes of Cyclea peltata was extracted using chromatographic techniques monitored using TLC and proton NMR studies. The pure compound isolated was subjected for proton NMR, carbon NMR, HSQC, HMBC, NOESY and COSY spectral experiments. Goal is to document the methods of isolation and NMR experiments involved in structural determination. The compound isolated were bisbenzyl isoquinoline alkaloid with head to head ether bond connection and identified as “Tetrandrine”. Eventhough tetrandrine is a known compound and is reported from many other plants, this time it is isolated and reported from Cyclea peltata (H.f & T).